Free convection and mass transfer flow past an infinite vertical porous plate with dufour and soret effects in a porus medium - Alam, Md. Shariful; Rahman, Mohammad Mansur (BRAC University, 2010)
A numerical solution of unsteady free convection and mass transfer flow is presented when a viscous, incompressible fluid flows along an infinite vertical porous plate embedded in a porous medium. Both the Dufour and Soret effects are considered when the fluid is not chemically reacting. Dimensionless velocity, temperature and concentration profiles are displayed graphically for different values of the parameters entering into the problem. The numerical values of the skinfriction coefficient, Nusselt and Sherwood numbers, which are of physical interest, are also tabulated.